A long-term permanent forest plot reveals a remarkable new species of Roucheria (Linaceae) from the Brazilian Atlantic Rainforest - Ottino, Giulia Cavalcanti; Amorim, André Márcio Araujo; Fraga, Claudio Nicoletti De; Fiaschi, Pedro; Silva, Sávio Pessoa; Silva, Luis Fernando Gonçalves Da; Soares-Silva, Joao Paulo; Marinho, Lucas Cardoso; Cardoso, Domingos; Viana, Pedro Lage (Phytotaxa, 2026)
A new species of Roucheria (Linaceae) was revealed through a vegetation monitoring campaign in a long-term permanent plot in Santa Teresa municipality, Espírito Santo state, southeastern Brazil. Here, we describe and illustrate Roucheria krenakiana, a canopy tree of the montane Atlantic Forest, which stands out for its obovate leaves with obtuse apex, crenulate margins and flowers with pale green petals and 3 to 5 styles, as well as congested axillary cymules, caducous stipules, and a glabrous ovary with 3–5 locules. We provide its description, illustration, phenology, a preliminary conservation assessment, and a discussion of its morphological relationships with closely related species. Our study highlights that long-term forest monitoring, when integrated with systematic voucher collecting, strengthens the documentation of poorly known lineages, and can reveal undescribed species.